Makna Pendidikan dalam Struktur Simbolis Kayon Ganesha: Sebuah Penelusuran Epistemologis dalam Konstruksi Semiotika Visual - Yasin Surya Wijaya (PANGGUNG, 2025)
This study aims to explore the educational values embodied in the visual symbolic structure of Kayon Ganesha, a creation by Enthus Susmono. The academic values represented in Kayon Ganesha are essential to be examined and utilized as a source of moral and character development for future generations. The research employs a descriptive, qualitative approach with a single-case study design. Data were collected from informants, settings, and documents through in-depth interviews, participatory observation, and content analysis. Data validity was tested using two techniques: data source triangulation and informant review. Data analysis followed a flow model consisting of data reduction, data display, and verification. The findings reveal that Kayon Ganesha consists of three structural parts, namely lower (palemahan), middle (lengkeh), and upper (pucuk), each containing symbols that represent the human journey toward ultimate truth through education. The figure of Lord Ganesha in Kayon Ganesha also comprises three parts, namely head, body, and feet, symbolizing the ideal qualities of a knowledgeable person. The implication of this study emphasizes that the educational values within Kayon Ganesha can serve as a source for character education based on local wisdom in the field of art and cultural creativity.